Islamic Religious Education Learning in the Era of Artificial Intelligence: Ethical and Pedagogical Challenges - Mohamad Din Hadi; Toto Dwi Pambudi; Muhammad; Nopi Sari (CV. Creative Tugu Pena, 2026)
The rapid advancement of artificial intelligence (AI) has significantly transformed educational practices, including Islamic Religious Education (IRE). While AI offers substantial potential to enhance learning effectiveness through personalization, adaptive instruction, and data-driven assessment, its integration into IRE raises critical ethical and pedagogical concerns. This study aims to examine the implications of AI for Islamic Religious Education, with particular attention to the challenges of maintaining ethical values and pedagogical integrity in technology-mediated learning environments. Using a qualitative literature review approach, this study analyzes relevant theoretical and empirical studies on AI in education, Islamic pedagogy, and Islamic ethics. The findings indicate that although AI can support instructional efficiency and learner engagement, it is limited in addressing the affective and spiritual dimensions central to IRE. Ethical issues such as data privacy, algorithmic bias, and the authority of religious knowledge, along with pedagogical challenges related to moral formation and teacher–student interaction, remain significant. The study concludes that a human-centered and ethically grounded integration of AI is essential to ensure that technological innovation aligns with the moral and spiritual objectives of Islamic Religious Education.